Productivity of Learning Management System in Organizational Development by Utilizing Smart Education - Faraasyatul Alam, Ghasa; Imron, Ali; Timan, Agus; ., Sultoni (KnE Social Sciences, 2023)
This study aims to describe the productivity of the learning management system in the context of organizational development by utilizing intelligent education that applies the latest technological innovations. The researcher uses a qualitative method with a descriptive approach, which will be the focus of the research, followed by interviews and observations, and qualitative data analysis such as manipulation and interpretation techniques that are related to a wider range. There are four research results, including (a) Learning management system as a lecture material platform; (b) Learning management system as assignment submission platform; (c) Learning management system as a discussion forum platform; and (d) Learning management system as a college exam platform. Keywords: learning management system, organizational development, smart education, educational management